Management of Corporate Social Responsibility (CSR) Funds of PT. Mustika Indah Permai - Melta Oktiana; Amaludin Amaludin; Tri Rusilawati (Gayaku Publisher, 2023)
Even though corporate social responsibility (CSR) is an industry obligation, sometimes there are differences between the realization and the role of local government. Therefore, it is necessary to develop a different model of CSR, especially for the coal mining industry in Lahat District. As a mining company, PT. Mustika Indah Permai in the partnership program, regional development, and regional development is the focus of this research, which aims to identify the realization, of the role of local government, and the creation of alternative CSR models. The local development CSR program which is a consequence of the mining industry shows, residents and environmental organizations are expected to track the nearest Government support. The model of cooperation between industry, residents and local government is the best alternative CSR model.